ENTREPRENEURS’ RESILIENCE TO NATURAL DISASTERS: STUDY ON EMERGING ENTREPRENEURS FROM FLOOD AFFECTED AREAS IN KERALA - Ms. Chippy Mohan, Dr. Rose Wine Joy (Chelonian Research Foundation, 2023)
This article aims to explore the resilience of entrepreneurs of the disaster, the investigations of the impact of some of the most important conditions for the sustainable development of the full potential of businesses affected by the 2018 floods in Kerala, India. The study was to carry out using a special questionnaire to be sent to local businesses affected by the flooding. The data were processed using IBM SPSS and PLS-SEM. The results showed that all the investigated structures have had a significant and positive effect on the ability of the business to be done. This article is a preliminary examination of the nature. Future research needs to take into account the additional terms and conditions for the stability of the organization. For a better understanding of the previous aspects of sustainable development, businesses can better evaluate their investments and to understand the skills and competencies that they need in order to be able to be a disaster. The organizational implications, with recommendations for public policy. Key words: resilience; natural disasters; entrepreneurs; flood